ANALYSIS OF DIFFERENCES IN AUDIT DELAY BETWEEN FINANCIAL COMPANIES AND NON-FINANCIAL COMPANIES - Al Ma'arif, Abd. Army; Nugrahani, Tri Siwi; Pronosokodewo, Baniady Gennody (CV. Fahr Publishing, 2024)
The purpose of this study is to determine the differences between financial and non-financial companies in terms of total current assets and audit delay. Current assets are types of assets that are estimated to be converted into cash within less than 1 year after the preparation of the financial statements. While audit delay is a period of time measured from the closing of the financial year to the issuance of the audit report. This study involved financial and non-financial companies listed on the IDX and included in the Kompas100 index consecutively during 2021–2022. The data analysis technique used in this study is the difference test with the Kruskal Wallis test. The results of the study indicate that there are differences between financial and non-financial companies in terms of current assets and audit delay.